Unveiling neurophobia: exploring factors influencing medical students, residents and non-neurologist physicians globally and its implications on neurology care – a systematic review and meta-analysis - Abdulrahman A AlZahrani; Bashaier G AlQahtani; Mawadda A Bayazeed; Mohammad Eid Mahfouz (BMJ Neurology Open)
Background Neurophobia, the fear of neurology, is a recognised global challenge in medical education and practice. This systematic review and meta-analysis aimed to quantify the prevalence of neurophobia among medical students, residents and non-neurologist physicians, identify contributing factors (including lack of basic science/clinical integration) and explore its implications for neurology care.Methods We systematically searched PubMed, Scopus and Google Scholar for studies published between 2000 and 2024 reporting on neurophobia. Two independent reviewers screened the studies, extracted data and assessed their quality using the Newcastle-Ottawa Scale. A random effects meta-analysis was performed to estimate the pooled prevalence of neurophobia. Heterogeneity and publication bias were tested statistically.Results Of the initial 1245 studies, 32 met the inclusion criteria. The pooled prevalence of neurophobia was 47.2% (95% CI: 39.8% to 54.6%), with significant heterogeneity (I²=98.7%, p<0.001). Subgroup analysis revealed a higher prevalence among medical students (52.3%, 95% CI: 44.1% to 60.5%) than residents and physicians (41.9%, 95% CI: 33.7% to 50.1%). Key contributing factors included the perceived complexity of neurology (OR: 3.2, 95% CI: 2.7 to 3.8) and inadequate exposure during training (OR: 2.8, 95% CI: 2.3 to 3.3). Individuals with neurophobia were less likely to consider a career in neurology (OR 0.32, 95% CI: 0.25 to 0.41).Conclusions Neurophobia affects a substantial proportion of medical trainees and practitioners globally, with variation across education and practice levels. Addressing contributing factors through targeted interventions may help mitigate neurophobia and improve neurological care. Further studies should focus on specific interventions.